2022
DOI: 10.3390/jmse10030393
|View full text |Cite
|
Sign up to set email alerts
|

Study of Hybrid Propulsion Systems for Lower Emissions and Fuel Saving on Merchant Ship during Voyage

Abstract: The hybrid propulsion system is a vehicle propulsion system with two or more sources of propulsion such as diesel, batteries, and other renewable energy. The use of hybrid propulsion systems is not new, and they have been adopted worldwide. There are many applications for hybrid propulsion systems, from powering land-based vehicles to marine vessels. With the success of hybrid propulsion systems, many large vessels still rely on two-stroke engines for power generation. In this paper, the benefits and feasibili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…The economic analysis in this paper considers the saving of gas on a voyage based on operating load characteristics. The shaft generator (Chin et al, 2022) can be used because the excess power could replace a diesel or dual-fuel generator at full load operating SOFC and ICE, which will save additional money.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The economic analysis in this paper considers the saving of gas on a voyage based on operating load characteristics. The shaft generator (Chin et al, 2022) can be used because the excess power could replace a diesel or dual-fuel generator at full load operating SOFC and ICE, which will save additional money.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, SOFCs demonstrate poor transient performance (Sapra et al, 2021). Chin et al (2022) reported that a full fuel cell system is still only viable for small to medium vessels, while a hybrid system is practical for large ships. Furthermore, Xing et al (2021) reported that reliability and durability will be achieved by integrating SOFC with batteries, photovoltaics, turbines, and engines, which can also maximize efficiency.…”
Section: Article Highlightsmentioning
confidence: 99%
“…While lessemitting propulsion systems can be retrofitted and partially replace ICEs, ships can also be redesigned implementing fully electrified powertrains. Research into zero-emission drive systems for marine applications is focused, in particular, on fuel cells and lithium-ion batteries (LIB) [4]. Ferries and other smaller vessels can already be powered entirely by batteries, as the energy density of LIBs is sufficient for these routes [5].…”
Section: Introductionmentioning
confidence: 99%